Highly Efficient Organosulfur and Lithium‐Metal Hosts Enabled by C@Fe3N Sponge. (7th December 2022) - He, Jiarui; Bhargav, Amruth; Sul, Hyunki; Manthiram, Arumugam
Abstract: Lithium‐organosulfur (Li‐OS) batteries, despite possessing high theoretical specific capacity, encounter a few practical challenges, including unsatisfactory lifespan and low active material utilization under realistic conditions. Here, diisoropyl xanthogen polysulfide (DIXPS) has been selected as a model organosulfur compound to investigate the practical feasibility of Li‐OS batteries under realistic conditions. A well‐designed freestanding carbon sponge decorated with Fe3 N nanoparticles (C@Fe3 N) is introduced into the Li‐OS cells as a scaffold for both Li and DIXPS. The lithiophilic property of the C@Fe3 N host guides uniform lithium deposition at the anode, and the catalysis of the DIXPS conversion reaction promotes the kinetics at the cathode. Impressively, the synergistic effect of C@Fe3 N leads to an extremely stable cycling performance over 1 000 cycles in a Li‐OS full cell under realistic conditions. Abstract : C@Fe3 N with both lithiophilic property and catalytic feature can simultaneously address the growth of dendritic Li in the anode and intermediates shuttling from the cathode. These synergistic effect of C@Fe3 N leads to an extremely stable cycling performance over 1 000 cycles in a Li‐organosulfur full cell with practically necessary parameters.